Powertrain system design of hydrogen fuel cell range-extended hybrid electric locomotive - WANG Xuhai; QI Hongrui; SUN Fengxia; ZHAO Zhifang (机车电传动)
With the continuous development of the application of new energy in the field of rail transit, the advantages of new energy hybrid locomotives in energy saving and emission reduction are more obvious, and the hybrid locomotive powered by hydrogen fuel cells and lithium batteries also has more and more extensive prospect. Based on the analysis of the operating conditions of the shunting locomotive, a hydrogen fuel cell range-extended hybrid locomotive powertrain system suitable for the operating conditions of the shunting locomotive was proposed, and the characteristics and advantages of the system were analyzed. Combined with the 700 kW hydrogen fuel cell hybrid locomotive developed by CRRC Datong Co., Ltd., the structural parameters, components and control methods of the powertrain system were introduced, focusing on the research and analysis of the matching design and energy management of the powertrain system. Through the research on the powertrain system, combined with the actual operation data of the locomotive, the feasibility of the range-extended hybrid locomotive power system was confirmed, and the follow-up research direction was proposed.